(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to describe the level of interest of students from Ganesha University of Education (UNDIKSHA) in playing badminton post-Covid-19 pandemic. The pandemic has restricted physical activities, including Student Activity Unit (UKM) activities, making it important to reassess students’ interest in sports. The method used is a descriptive quantitative approach with survey techniques. Data were obtained from 30 students through a Likert scale questionnaire that measures four indicators of interest: pleasure, attention, interest, and involvement. The data analysis technique used is descriptive analysis. The analysis results show that 76.67% of respondents expressed great enjoyment in playing badminton, 83.33% actively followed related information, and 73.33% are committed to practicing again. These findings indicate that students’ interest in badminton remains high even though it had been paused during the pandemic. Therefore, the management of student organizations needs to optimize training programs and institutional support so that students’ interest can be transformed into sustainable active participation.